30-Gb/s Optical Link Combining Heterogeneously Integrated III–V/Si Photonics With 32-nm CMOS Circuits - Dupuis, Nicolas; Lee, Benjamin; Proesel, Jonathan; Rylyakov, Alexander; Rimolo-Donadio, Renato; Baks, Christian; Abhijeet, Ardey; Schow, Clint; Ramaswamy, Anand; Roth, Jonathan; Robert, Guzzon; Koch, Brian; et al. (Institute of Electrical and Electronics Engineers Inc., 2015)
We present a silicon photonics optical link utilizing heterogeneously integrated photonic devices driven by low-power advanced 32-nm CMOS integrated circuits. The photonic components include a quantum-confined Stark effect electroabsorption modulator and an edge-coupled waveguide photodetector, both made of III-V material wafer bonded on silicon-on-insulator wafers. The photonic devices are wire bonded to the CMOS chips and mounted on a custom PCB card for testing. We demonstrate an error-free operation at data rates up to 30 Gb/s and transmission over 10 km at 25 Gb/s with no measured sensitivity penalty and a timing margin penalty of 0.2 UI.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84923347115&partnerID=40&md5=5880e003b3aaac1af96bfc0568a8fa98
Keywords: Circuitos; Fotodetectores; Fotónica; Potencia eléctrica; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering